The integration of shade-sensitive annual crops in Musa spp. plantations in South Kivu, Democratic Republic of Congo - Ntamwira, Jules Bagula; Ocimati, Walter; Kearsley, Elizabeth; Safari, Nancy; Bahati, Liliane; Amini, Daniel; Kanyenga Lubobo, Antoine; Waswa, Boaz Shaban; Blomme, Guy (MDPI, 2021)
Small-holder banana fields are often intercropped with various annual crops to optimize land-use in East and Central Africa, a practice severely constrained by light availability under the banana canopy. Light availability is not a major constraint in newly established banana fields, giving a window of opportunity to target light-demanding annual crops before shifting to more shadetolerant crops. This study investigated the performance of climbing and bush beans and the vegetable amaranth in banana fields with varying shade levels across three sites in the South Kivu province, DR Congo. These crops were selected for their highly nutritious and good market value and the added benefit of nitrogen fixation for the legumes. We show that both grain legumes and vegetable amaranth can achieve reasonable yields during a first annual cropping season in newly established banana fields, irrespective of the plant density. Declines in yield occurred during a second cropping season in more densely spaced banana fields (2 2 m and 2 3 m). A greater decline occurred in amaranth and its cultivation should be limited to the first annual cropping season or to less dense banana fields. The legumes could be extended to a second cropping season with reasonable yield. Significant variability in amaranth and legumes performance was observed across sites, with rapid yield declines occurring under more fertile soil conditions due to fast banana growth/canopy formation and under more vigorous cultivars. The choice of banana spacing will need to be tailored to the banana cultivar, soil conditions and the farmers’ objectives.